Simultaneous Nbs1 and p53 inactivation in neural progenitors triggers high-grade gliomas - Reuss, David; Downing, Susanna M.; Camacho, Cristel V.; Wang, Yong-Dong; Piro, Rosario M.; Herold-Mende, Christel; Wang, Zhao-Qi; Hofmann, Thomas G.; Sahm, Felix; Deimling, Andreas von; McKinnon, Peter J.; Frappart, Pierre-Olivier (Neuropathology & applied neurobiology, 2023)
Aims Nijmegen breakage syndrome (NBS) is a rare autosomal recessive disorder caused by hypomorphic mutations of NBS1. NBS1 is a member of the MRE11-RAD50-NBS1 (MRN) complex that binds to DNA double-strand breaks and activates the DNA damage response (DDR). Nbs1 inactivation in neural progenitor cells leads to microcephaly and premature death. Interestingly, p53 homozygous deletion rescues the NBS1-deficient phenotype allowing long-term survival. The objective of this work was to determine whether simultaneous inactivation of Nbs1 and p53 in neural progenitors triggered brain tumorigenesis and if so in which category this tumour could be classified. Methods We generated a mouse model with simultaneous genetic inactivation of Nbs1 and p53 in embryonic neural stem cells and analysed the arising tumours with in-depth molecular analyses including immunohistochemistry, array comparative genomic hybridisation (aCGH), whole exome-sequencing and RNA-sequencing. Results NBS1/P53-deficient mice develop high-grade gliomas (HGG) arising in the olfactory bulbs and in the cortex along the rostral migratory stream. In-depth molecular analyses using immunohistochemistry, aCGH, whole exome-sequencing and RNA-sequencing revealed striking similarities to paediatric human HGG with shared features with radiation-induced gliomas (RIGs). Conclusions Our findings show that concomitant inactivation of Nbs1 and p53 in mice promotes HGG with RIG features. This model could be useful for preclinical studies to improve the prognosis of these deadly tumours, but it also highlights the singularity of NBS1 among the other DNA damage response proteins in the aetiology of brain tumours.